2023
DOI: 10.1101/2023.08.07.552336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptome landscape of developing fetal gonads defines somatic cell lineage specification in humans

Abstract: Gonad development is an exciting model to study cell fate commitment. However, the specification and differentiation of somatic cell lineages within the testis and the ovary are incompletely characterized, especially in humans. In fact, a better understanding of sex determination first requires the identification of all the cell types involved and of their dynamic expression programs. Here we present a comprehensive analysis of approximately 128,000 single cells collected from 33 fetal testes and ovaries betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Recently, the IOR has gained attention as a newly described progenitor for supporting cells of the murine gonad (Mayère et al, 2022). Recent single cell transcriptomics studies have also identified cells of the RO within human fetal gonads (Lardenois et al, 2023; Taelman et al, 2022). We reported that the entire RO expresses high levels of PAX8, and chose to use this as a marker to visualize and characterize cells of the RO.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the IOR has gained attention as a newly described progenitor for supporting cells of the murine gonad (Mayère et al, 2022). Recent single cell transcriptomics studies have also identified cells of the RO within human fetal gonads (Lardenois et al, 2023; Taelman et al, 2022). We reported that the entire RO expresses high levels of PAX8, and chose to use this as a marker to visualize and characterize cells of the RO.…”
Section: Introductionmentioning
confidence: 99%